KOLEKTIF DAN MENJADI-KOLEKTIF: Evolusi Wacana Kolektif Seni Rupa di Jakarta, 2000 – 2022 - Martin Suryajaya; Nyak Ina Raseuk; Amy Zahrawaan (LIPI Press, 2023)
Art collective is a form of artistic subjectivity that has become increasingly common in Indonesian urbanlandscape in the last two decades. By focusing on seven collectives (Gudskul, ruangrupa, Forum Lenteng, Serrum,Graphic Huru Hara, Gardu House and Cut and Rescue), this article is a mapping of the discursive evolution onart collectives in Jakarta during 2000 – 2022. The method used were distant reading and social network analysisof the interactions of these art collectives on social media (Twitter and Instagram) as well as a number of journalsand books they publish. Social network analysis were applied to examine the pattern of mentions between socialmedia accounts in discussing art collective issues. Distant reading were also applied to the posts of these accounts,the various journals, and books published collectively. Through these method, three main things were found: 1)the emergence of art collectives in Jakarta in the early 2000s was not accompanied by a conscious consolidationof collectivities based on multiplicities, but rather on individuality, 2) the shift of focus from “alternative spaces”to “ collective” and “lumbung” (the commons) emerged from the need for network consolidation and communalresource management, and 3) the focus on “lumbung” led to a return to a number of traditional features of sanggarand a more programmatic conception of art